F O V Acheson and Maori Customary Law - Boast, Richard P (Victoria University of Wellington Law Review, 1999)
This article briefly discusses the life and views of Frank Acheson, Judge of the Wanganui and Tai Tokerau Divisions of the Native Land Court. Professor Boast discusses Judge Acheson's Jacob Joseph Scholarship essay, which encompasses Judge Acheson's views on Maori customs. Judge Acheson is described as an activist judge and something of a tragic figure who has been largely forgotten by New Zealand history. However, Professor Boast concludes that Judge Acheson's work shows that the development of New Zealand jurisprudence is not necessarily as simplistic and narrowly positivist as is sometimes assumed.